The open data imperative - Professor Geoffrey Boulton (Insights: The UKSG Journal, 2014)
The information revolution of recent decades is a world historical event that is changing the lives of individuals, societies and economies and with major implications for science, research and learning. It offers profound opportunities to explore phenomena that were hitherto beyond our power to resolve, and at the same time is undermining the process whereby concurrent publication of scientific concept and evidence (data) permitted scrutiny, replication and refutation and that has been the bedrock of scientific progress and of ‘self-correction’ since the inception of the first scientific journals in the 17th century. Open publication, release and sharing of data are vital habits that need to be redefined and redeveloped for the modern age by the research community if it is to exploit technological opportunities, maintain self-correction and maximize the contribution of research to human understanding and welfare.